Electron-Transfer-Induced Intramolecular Heck Carbonylation Reactions Leading to Benzolactones and Benzolactams - Fukuyama, Takahide; Bando, Takanobu; Ryu, Ilhyong (Synthesis, 2018)
A metal-catalyst-free intramolecular Heck carbonylation reaction of benzyl alcohols and benzyl amines with carbon monoxide under heating at 250 °C affords the corresponding benzolactones and benzolactams in good to excellent yields. A hybrid radical/ionic chain mechanism, involving electron transfer from radical anions generated by nucleophilic attack of alcohols or amines on intermediate acyl radicals, is proposed.
Keywords: carbonylation; electron transfer; radical reactions; metal-free; lactones; lactams